122k views
23 votes
Solve.

6x−13=2x+7


2

3

5

6

2 Answers

12 votes

Answer:

Explanation:

6x−13=2x+7

Inverse operation:

6x into a negative then subtract it by 2x

2x - 6x = -4

Change 7 into a negative then subtract it by -13

-13 - 7 = -20

-20 = -4x

Divide:

-20 = -4x

_______

-4 -4

-20/-4 = 5

Answer:

5 = x or x = 5

User Rishabh Gupta
by
4.5k points
6 votes

Answer: x = 5

Step-by-step explanation:To solve this you first need to collect the like terms 6x-2x=7+3. Add those 4x=20. After that you need to divide both sides. Then you will get you solution.

User Femibyte
by
5.2k points